Kidney Health for All – Bridging the gap to better kidney care in Africa - Tannor, Elliot Koranteng; Nlandu, Yannick Mayamba; Elrggal, Mohammed E; Chika, Onu Ugochi; Nzana, Victorine (African Journal of Nephrology, 2022)
Introduction: The prevalence of chronic kidney disease (CKD) in Africa is generally higher than global averages. Moreover, the management of patients with CKD suffers huge disparities compared to the rest of the world. We reviewed the literature on the major challenges in the management of kidney disease in Africa and suggest ways to bridge the gap for better kidney care on the African continent. Results and recommendations: The prevalence of CKD in Africa is 15.8%. Kidney failure is associated with increased morbidity and mortality as a result of limited infrastructure and out-of-pocket payment for renal replacement therapy in most parts of the continent. The increasing prevalence of CKD results from epidemiological transition with increasing non-communicable diseases (NCDs) and established communicable diseases. Furthermore, Africa has unique risk factors and causes of kidney disease such as sickle cell disease, APOL1 risk alleles, and chronic infections such HIV, and hepatitis B and C. Challenges facing kidney care in Africa include poverty, weak health systems, inadequate primary health care, misplaced priorities by political leaders, a relatively low nephrology workforce, poor identification of acute kidney injury (AKI), low transplantation rates as well as a lack of sustainable prevention policies and renal registries. To bridge the gap to better kidney care, there should be more community engagement, advocacy for increased government support into kidney care, comprehensive renal registries, training of a greater nephrology workforce, task shifting of nephrology services to non-nephrologists, expanded access to renal replacement therapy and promotion of organ donation. Conclusion: Africa needs greater investment in kidney health.